PENGERUH WAKTU KERJA TERHADAP KADAR HEMOGLOBIN DAN JUMLAH SEL DARAH MERAH PETUGAS SHIFT MALAM SPBU JATI PARIAMAN - Muhammad Saka Abeiasa (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2020)
Based on reports from the World Health Organization (WHO), the prevalence of anemia in the world is still quite high with an incidence rate of 2.3 billion, in Asia it is known that the prevalence of anemia is still very high, it is known that 85% of anemia sufferers are women and children, about 50% of these events are iron deficiency anemia. This research uses descriptive analytic method using a cross sectional approach to see the relationship of events at one time. The study was conducted in March 2018 at the Pariaman city gas station. The sample was taken using a total sampling method with a total sample of 15 Jati gas station operators with night shift work. The data collection method begins with observing and interviewing the operator to get operator schedule data. Afterwards, each operator who is on a night shift is examined by taking a sample of peripheral blood through the fingertips. The blood obtained was analyzed using the Neubeur technique to see the number of red blood cells, while for Hb levels using the EasyTouch GCHb tool. From the results of the above table, it is known that the p value (0.00) shows that the time of night work has an influence on hemoglobin levels and the number of red blood cells in the Pariaman gas station. It can be concluded that there is a significant influence between the time of night work on hemoglobin levels and the number of red blood cells at the jati gas station night shift operator.